Basic Psychological Needs Satisfaction Mediates The Role of Work Climate and Early Childhood Education Teachers’ Intrinsic Work Motivation in Rural Areas - Hanggara Budi Utomo; Dema Yulianto; Isfauzi Hadi Nugroho; Ridwan Ridwan; Duanty Syaharani (Universitas Ahmad Dahlan, 2023)
One of the problems that has become a serious challenge in the world of education is improving the quality of education in rural areas, which is disadvantaged, outermost, and frontier. Teachers’ intrinsic work motivation is an important indicator of the quality of the teachers’ work to bring out qualified performance. This study aimed to investigate the role of basic psychological needs satisfaction as the mediator between work climate and intrinsic work motivation of early childhood education teachers in rural areas. A total of one hundred and seven early childhood education teachers participated in this research by filling out questionnaires on organizational climate, basic psychological needs satisfaction, and interest or pleasure questionnaires from the intrinsic motivation inventory. Data analysis techniques used IBM SPSS 22 and Smart PLS 3. The results of the study reveal that the work climate is a factor that influences basic psychological needs satisfaction and intrinsic work motivation. Furthermore, the results of the study also show that basic psychological needs satisfaction affects the intrinsic work motivation of teachers and becomes a factor that mediates the role of work climate on the intrinsic work motivation of early childhood education teachers in rural areas. Optimizing the mediating role of basic psychological needs satisfaction can bring a more positive atmosphere for the teacher's work climate, increasing the teacher's teaching assignments and work motivation. The results also show that basic psychological needs satisfaction affects the intrinsic work motivation of teachers and serves as a factor that mediates the role of work climate on the intrinsic work motivation of early childhood teachers in rural areas